Paradigm Mapping of Ecological Anthropology Theories: Analysis of Development from Classical to Contemporary - Sarlan Adijaya (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: The development of ecological anthropology has undergone significant paradigm shifts from the classical to the contemporary period. These shifts reflect changing perspectives on the relationships among humans, environments, power structures, and non-human entities within socio-ecological systems. Objectives: This study aims to provide a comprehensive overview of the periodization and major transformations within ecological anthropology, and to identify the evolving conceptual directions, analytical focuses, and methodological approaches across different historical phases. Methods: A systematic review combined with descriptive-comparative analysis was employed to examine key literature in ecological anthropology, covering theories, analytical orientations, and ethnographic practices from the 1950s to the present. Results: The review identifies five major paradigms: ecological determinism, cultural ecology, political ecology, historical ecology, and multispecies anthropology. The periodization shows a shift from classical environmental determinism (1950–1970), to modern approaches integrating power relations and historical dimensions (1970–1990), to contemporary perspectives that acknowledge non-human agency and global issues (1990–present). The analysis reveals three critical transformations: (1) a shift in the scale of analysis from local to integrated global–local perspectives, (2) a diversification of research focus from passive adaptation to active socio-ecological transformation, and (3) a methodological evolution from single-site ethnography to transdisciplinary multi-site ethnography. The findings also illustrate a broader transition from “culture designed by nature” to “culture designed by power,” a hallmark of the Anthropocene era. Conclusion: This study highlights the importance of an integrative approach in ecological anthropology to adequately capture the multi-scalar complexity of contemporary socio-ecological systems. Such an approach is essential for understanding the interplay of power, history, cross-species relations, and global challenges that increasingly shape human life in the Anthropocene.